Pathogen and pest risks to vegetatively propagated crops in humanitarian contexts: Geographic priorities for Cameroon and Ethiopia - Mouafo-Tchinda, R.; Etherton, B.; Plex Sula, A.; Andrade-Piedra, J.L.; Ogero, K.; Omondi, Bonaventure Aman Oduor; McEwan, M.; Tene, P.; Harahagazwe, D.; Cherinet, M.; Gebeyehu, S.; Sperling, L.; et al. (Cold Spring Harbor Laboratory, 2024)
Cameroon and Ethiopia face complex humanitarian crises that disrupt the production of key food security crops like banana and plantain, cassava, potato, and sweetpotato. These vegetatively propagated crops are prone to the buildup of pests and diseases causing seed degeneration. In this study, we address seed degeneration in the context of natural and human-driven crises, to provide insights that can guide the decisions of humanitarian groups to reduce seed degeneration. We identified locations in Cameroon and Ethiopia that are likely to be particularly important for pathogen and pest spread in cropland network analyses. We analyzed cropland networks in each country to develop a map of locations that are candidate priorities for disease and pest management and surveillance. For example, locations in central and western Oromia, Ethiopia, are likely important for potato pathogen and pest spread given the locations' roles in the cropland network. Next, we used expert knowledge elicitation to characterize crop health risk in these systems. For example, experts reported with high consensus that there are formal and informal imports of cassava from Gabon to Cameroon, which pose a risk to cassava production in Cameroon through seedborne pathogens. These results can inform regional and national surveillance and management strategies and provide a baseline for more in-depth studies in Cameroon and Ethiopia. The results can also inform decision-making in the humanitarian sector, for designing on-the-ground actions to avoid unintentional spread of pathogens and pests during agricultural recovery interventions.